International business in the information and digital age - Tulder, Rob van; Verbeke, Alain; Piscitello, Lucia (Progress in international business research, 2018)
This volume is dedicated to Lorraine Eden for herlifetime contributions to IB scholarship. Her research, spanning severaldecades, has addressed many interdisciplinary and societal themes at the heartof the IB field. The story of her intellectual journey -- strongly influenced bythe coming of age of the fourth industrial revolution -- is shared in the opening chapterof this volume. This thirteenth volume in the PIBR series covers an increasingly importantarea of research for International Business (IB) scholars: the role ofmultinational enterprises (MNEs) in the digital and information age. A limitednumber of MNEs now dominate the landscape of the digital age, but almost allinternationally operating firms are being affected by prevailing trends. How totake stock of these trends? How to develop resilient international businessmodels? How to regulate? The digital age presents new opportunities but alsomajor challenges for established and emerging MNEs alike. This volume brings together papers from leading IB scholars and from academics in adjacent disciplines such as economic geography,international relations and political science, strategic management, andtechnology studies. Four dimensions of the information and digital age are analyzed using an IB angle: Trends and theories in the information age Entrepreneurial strategies in the informationage; Functional strategies in the information age; Industry 4.0.